Optimal solution of assignment problem in Rojam manufacturing company - Mohamad, Nor Fatihah; Abdul Rahim, Mohd Kamarul Irwan (2015)
This research is about assignment problems consist to determine one of the special cases of transportation problems.The assignment problem is a of combinatorial optimization problems in the branch of optimization of or operation research in the mathematics.This research is trying to dig a lot of information by looking at the statistics of the management department with problems whose structure are identical with assignment problems in manufacturing company, which for separate jobs and the cost of assign each job to each person. This study comes out with two elements as an objective which is to minimize total cost of assignment problem in manufacturing company and to maximize the profit in manufacturing company.This study will conduct visit to a manufacturing company and the data will be collected from all employees in departments such as quality department, operation department, human resources department, marketing department and others.This study using quantitative methodology and the data will be analysed using the AMPL model to solve the assignment problem in the manufacturing company.The findings of this research are showing the vehicle assignment problem and the computational procedure, which lead to an optimal solution of the problem. It can reduce the total cost and increases the quality performance the workers.